Atrial septostomy in the treatment of severe pulmonary arterial hypertension. Issue 9 (28th August 2003) - Reichenberger, F; Pepke-Zaba, J; McNeil, K; Parameshwar, J; Shapiro, L M
Abstract : Background: Atrial septostomy (AS) may improve symptoms and haemodynamics in patients with severe pulmonary arterial hypertension (PAH). Methods: Twenty AS performed in 17 patients with severe progressive PAH (13 primary pulmonary hypertension, two collagen vascular disease, one thromboembolic disease, one vaso-occlusive disease) were analysed. Seven patients were in NYHA class III and 10 in NYHA IV. Fifteen patients were on long term prostanoid treatment. AS was performed under fluoroscopy using graded balloon technique. Results: AS improved clinical symptoms and increased the cardiac index from 1.8 to 2.2 l/min/m 2 and systemic oxygen transport from 263.2 to 329.6 ml/min/m 2 (p<0.001). Procedure related complications included one non-fatal atrial puncture and one unsuccessful septal puncture. Four patients died within 1 week of surgery from uncontrolled tachyarrhythmia (n=1), severe hypoxaemia (n=1), and multiorgan failure (n=2). One further patient died after voluntarily discontinuing renal dialysis. Twelve patients are alive 5–17 months after the operation with five patients undergoing heart-lung transplantation. There were no differences in haemodynamic and functional parameters between the non-survivors and the mid term survivors. However, the non-survivors were significantly older (52 v 36 years, p<0.01) and had a significantly lower creatinine clearance rate (70 ml/min v 48 ml/min, p<0.05). Conclusion: Atrial septostomy improves clinical symptoms, cardiac index, and systemic oxygen transport and has the potential to influence the prognosis in selected cases of severe PAH.